THE EFFECT OF TAX UNDERSTANDING AND TAXPAYER AWARENESS ON THE PERCEPTION OF TAX REVENUE AMONG MSMES AT KPP PRATAMA CIAWI (A CASE STUDY IN CIBUNGBULANG DISTRICT) - Susilawati; Darul Fahmi; Ganefo Sudirman (International Journal Management and Economic, 2026)
This study aims to examine the effect of tax understanding and taxpayer awareness on the perception of tax revenue among Micro, Small, and Medium Enterprises registered at KPP Pratama Ciawi, particularly in Cibungbulang District. The research adopts a quantitative associative approach using primary data collected through structured questionnaires distributed to MSME actors. The data were analyzed using multiple linear regression to identify both partial and simultaneous effects of the independent variables on the dependent variable. The findings indicate that tax understanding does not have a significant effect on the perception of tax revenue, while taxpayer awareness has a positive and significant influence. Simultaneously, both variables significantly affect the perception of tax revenue. These results suggest that enhancing internal awareness plays a more critical role than cognitive understanding in shaping positive perceptions toward tax revenue among MSMEs. The study provides implications for tax authorities to strengthen awareness-based education and outreach programs.